Procedural Motor Skills and Interference in the Academic Life Routine of a Group of Schoolchildren With Signs and Symptoms of ADHD - Rubio-Grillo, María Helena; Salazar-Torres, Lenis Judith; Rojas-Fajardo, Aida (Revista colombiana de psiquiatría, 2014)
There is a rising prevalence of attention deficit and hyperactivity disorder (ADHD) in educational institutions. Difficulties in academic development manifest as: slow information processing, difficulty in planning and working memory, difficulty staying focused, struggle selecting data or stimuli relevant to the implementation and completion of tasks. If adequate educational measures and specialized intervention are not established, the characteristics may affect instrumental learning. The aim of this study is to identify procedural motor skills that interfere with academic activities in a group of elementary school children, with signs and symptoms of ADHD. Descriptive study including children from 2nd to 4th grade of elementary school in which teachers detected signs and symptoms of ADHD by using questionnaires and observing school behavior. Procedural motor skills were identified and it was evidenced which skills interfered in the execution of academic activities. The population that showed inattention and hyperactivity behaviors manifested behavioral problems, low academic performance, and in turn, greater difficulty in postural skills and skill related with organization of space and objects, which interfered with the activities of daily living academic routine, as expected. The assessment of procedural motor skills allowed to determine specific difficulties in routine activities, and to agree on intervention strategies in the classroom.